Potential Antibacterial of Binahong Leaf Extract Against Bacteria Enterococcus faecalis ATCC® 29212™ (in vitro): Potensi Antibakteri Ekstrak Daun Binahong Terhadap Bakteri Enterococcus faecalis ATCC® 29212™ (in vitro) - Nasution, Minasari; Ameta Primasari; Ika Astrina; Siregar, Arfi Luthfiyah (TALENTA, 2022)
Binahong is a plant widely found in Indonesia and has been used for generations, but only by inheritance without much optimal research. Enterococcus faecalis is bacteria that cause many problems in the oral cavity such as periradicular lesion. The purpose of this study was to determine the zone of inhibition, Minimum Bactericidal Concentration (MBC), and Minimum Inhibitory Concentration (MIC) of Binahong leaf extract against bacteria Enterococcus faecalis ATCC® 29212TM concentrations of 100%, 90%, 80%, 70%, and 60%, chlorhexidine 0,2% as positive control and DMSO as a negative control. The experimental method used for the research with a post-test only control group design, pure bacteria prepared in the microbiology laboratory, and Binahong leaf extract used in the chemical laboratory of the Faculty of Mathematics and Natural Sciences (FMIPA) at the University of North Sumatera. Five treatments of Binahong leaf extract concentration were tested as samples four times. MBC and MIC measurements of Binahong leaf extract against Enterococcus faecalis ATCC® 29212TM were exchanged for each concentration. Mueller Hinton Agar (MHA) and Nutrient Broth incubated for 24 hours at 37°C. The ANOVA test data is analysed, followed by the Post Hoc test. The average inhibition zone of 100% concentration was 14.19 mm, 90% was 12.25 mm, 80% was (10.19 mm), 70% was 8.81 mm, 60% was 0.00 mm, chlorhexidine 0,2% was 20.88 mm, and DMSO was 0.00 m). The conclusion is that the best inhibition zone has a concentration of 100%, MBC was at 100%, and MIC was at 60%.